Adherence to digital pregnancy care – lessons learned from the SMART start feasibility study - Jäger, Katharina; Nissen, Michael; Leutheuser, Heike; Danzberger, Nina; Titzmann, Adriana; Pontones, Constanza; Goossens, Chloë; Ziegler, Philipp; Uhrig, Sabrina; Häberle, Lothar; Bleher, Hannah; Kast, Kristina; et al. (npj Digital Medicine, 2025)
The World Health Organization increasingly highlights the role of digital health technologies in supporting prenatal care. Despite this potential, the real-world implementation of such technologies remains limited, even in high-income countries with established analog systems. We developed a comprehensive digital pregnancy care framework, SMART Start and evaluated it in a prospective study involving 528 pregnant individuals in Germany. This study is registered at the German Clinical Trials Register (DRKS00036867). Participants were equipped with a mobile app and self-examination technologies. The mobile app featured study functionality, pregnancy-related questionnaires, digital maternity records, and pregnancy-supportive content. Self-examination technologies included a standard care kit for home measurements of routine prenatal care parameters (weight, blood pressure, urinalysis), and an innovative kit with novel sensors (smartwatch, sleep analyzer). Here, we analyzed the adherence to digital pregnancy care and present the lessons learned from a clinical and technical perspective. Among all participants, 49% engaged with at least one digital package. Weekly weight tracking reached adherence rates up to 67% in the first 14 weeks. Adherence to blood pressure and urinalysis measurements was lower, peaking at 20 and 28%, respectively, but remained stable over time. Questionnaire completion rates varied in dependence on their length and complexity. 31% of users disengaged at the time of registration. While overall retention time did not significantly differ across participant subgroups (all p > 0.05), adherence analyses revealed meaningful group-level differences in engagement with specific self-examination protocols. This discrepancy underscores that continued participation does not necessarily imply consistent engagement with all components of the digital care model. The adherence to the study schedule demonstrated that pregnant individuals are generally willing and capable of engaging in home-based, multimodal self-monitoring; however, the importance of adaptive scheduling, patient-centered feedback, agile development, and interdisciplinary collaboration should be addressed by future studies. The presented SMART Start framework offers a pathway towards data-driven, personalized pregnancy care while potentially reducing the demand for conventional healthcare infrastructur

Characteristics and decision making of hospital report card consumers: lessons from an onsite-based cross-sectional study - Emmert, Martin; Kast, Kristina; Sander, Uwe (Health Policy, 2019)
Background Hospitals report cards (HRCs) have had little impact on the hospital choice of patients. Thus, health policy makers should learn more about HRC consumers to better understand how to present and target hospital-related quality information. Objective We sought to learn more about consumers of HRCs and determine the impact of the complexity and tailoring of HRCs on the hospital choice. Methods We used primary data drawn from an onsite-based survey, conducted in 2017 at Germany’s premier portal, Weisse Liste (N = 635). We performed hierarchical multivariate logistic regression models to identify main predictors associated with hospital choices. Results HRC consumers differ from the national online population and the national population in general. Eighty percent of those patients or family members, who have used a HRC before, confirmed an impact on the hospital choice. The quality of hospital choices decreased with an increasing level of complexity (p < .001); the latter was identified as a significant predictor for making good choices. However, tailoring HRCs did not have an impact on the quality of the hospital choice (p > .05). Conclusions HRCs have a significant impact on the hospital choice among report card consumers. Health policy makers might focus on decreasing the level of complexity; this, more than tailoring report cards, may help consumers make good hospital choices.
Keywords: Public reportingHospital report cardsTailoringSurvey analysis

Deutsche Vergleichsportale für Hebammensuche: ein hilfreiches Entscheidungsinstrument für Schwangere? German comparison portals for midwife searches: a helpful decision-making tool for pregnant women? - Kast, Kristina; Oderbein, Anja; Karch, Julia; Schöffski, Oliver (Prävention und Gesundheitsförderung, 2024)
Hintergrund und Zielsetzung Vergleichsportale können helfen, einen geeigneten medizinischen Leistungserbringer, wie z.B. eine Hebamme, zu finden. Das Ziel dieser Arbeit ist, solche Portale in Deutschland zu analysieren und ihren Nutzen für Schwangere zu beurteilen. Methodik Über die Suchmaschine Google wurden 25 deutsche Webseiten mit Hilfe der PRISMA-Systematik identifiziert, die eine Hebammensuche in Deutschland ermöglichen. Anhand einer Stichprobe aus 550 Hebammenprofilen wurden dort der Inhalt (Struktur-, Prozess- und Ergebnisqualität gemäß dem Qualitätsmodell von Avedis Donabedian) und die Funktionen der Webseiten (z.B. Filtern, Sortieren, Vergleichen) untersucht sowie der Nutzen der Vergleichsportale anhand einer Checkliste mit fünf Kategorien (z.B. Sozialkompetenz) evaluiert. Ergebnisse Die Webseiten konzentrieren sich in den meisten Fällen ausschließlich auf Hebammensuche (92 %) und werden durch Hebammen (60 %) oder ihre Verbände (16 %) mit Informationen versorgt. Ein Drittel (n = 8) der Webseiten gibt keine Informationsquelle an. Überwiegend sind Elemente der Strukturqualität und Möglichkeiten zum Suchen und Filtern von Informationen vorhanden. Mehrere bedeutende Informationen (z.B. Qualifikation, Ergebnisqualität) und Funktionen (z.B. Vergleichen, Bewerten) sind ungenügend vorhanden. Bei der Nutzenbewertung erreichten die Webseiten insgesamt 114 von 400 möglichen Punkten, was einem Abdeckungsgrad von weniger als 30% entspricht. Diskussion und Fazit Insgesamt konnte festgestellt werden, dass Vergleichsportale in der aktuellen Form für Schwangere bei der Suche nach einer geeigneten Hebamme nicht hilfreich sind und nicht das Potenzial haben, die Versorgung zu verbessern. Für eine adäquate Qualitätsberichterstattung auf Vergleichsportalen, müssen Informationen aus unabhängigen Quellen konsequent dargelegt werden. Neben strukturellen Informationen müssen auch „harte Fakten“ veröffentlicht werden und Bewertungen durch Patientinnen sollten möglich sein. Darüber hinaus sollten für eine bessere Handhabung der Informationen weitere Komplexität reduzierende Funktionen eingebaut werden. Background and objective Comparison portals for health care providers search can help pregnant women to identify a suitable midwife. In the present study, we aimed to analyze such websites in Germany and to evaluate their benefit for pregnant women. Methodology Via search engine Google and using the PRISMA reporting statement, we identified 25 German websites that allow for a midwife search in Germany. After drawing a sample of 550 midwife profiles on those websites, we collected data on their content (structural, process, and outcome quality dimensions suggested by Avedis Donabedian) and functions (e.g., filtering, sorting, comparing), and evaluated the benefit of the websites via a five-category-checklist (e.g., social competence). Results Most websites focus exclusively on midwife search (92%) and are provided with information by midwives (60%) or their associations (16%). One third (n = 8) of the websites do not provide information sources. Predominantly, elements of structural quality and options for searching and filtering of information are available. Several relevant information (e.g., qualification, outcome quality) and functions (e.g., comparing, ratings) are insufficiently available. In the benefit assessment, the websites achieved a total of 114 out of 400 points possible, which is equivalent to a coverage rate of less than 30%. Discussion and conclusion In the current form, comparison portals are not only less helpful for pregnant women when choosing a midwife, but also lack the potential to improve the quality of care. For appropriate quality reporting on comparison portals, information should be independent and transparent. In addition to structural quality information, “hard facts” must also be displayed and patient ratings should be possible. Furthermore, additional complexity-reducing functions should be integrated to make the information easier to use.
Keywords: Qualitätsberichterstattung; Versorgungsqualität; Hebammenleistungen; Medizinische Vergleichsportale; Webseitenanalyse; Public Reporting; Quality of Care; Midwife services; Medical Comparison portals; Website analysis

Economic evidence with respect to cost-effectiveness of the transitional care model among geriatric patients discharged from hospital to home: a systematic review - Kast, Kristina; Wachter, Carl-Philipp; Schöffski, Oliver; Rimmele, Martina (European Journal of Health Economics, 2021)
Background The German hospital-to-home discharge management of geriatric patients has long been criticized. The implementation of the American Transitional Care Model (TCM) could help to reduce readmissions and costs. The objective of this review was to check the scientific evidence of the cost-effectiveness of the TCM. Methods A systematic literature search in six databases for the time period of 26 years was conducted. The studies had to meet all pre-defined inclusion criteria. The data extraction is based on a criteria chart from literature. The methodological quality was assessed using the tools of the National Heart, Lung, and Blood Institute as well as the Consensus Health Economic Criteria list. The results transferability to German health care system was explained based on the criteria from the literature. Results Three American studies met all criteria. They showed partial cost analyses but no full economic analyses. It could be assumed that the economic effect of the TCM changes over time. The costs of a care coordinator could not be determined because few detailed information was reported. The TCM may have negative consequences for hospitals. The results are not transferable to Germany. Conclusion There is no scientific evidence for the cost-effectiveness of the defined TCM. The optimal TCM duration still needs to be clarified. A detailed overview with units and prices and an additional consideration of the hospital perspective could help to make the information more transparent when deciding about the TCM implementation. A full economic analysis under German conditions or for similar European countries is necessary.
Keywords: Transitional care Geriatric patients Hospital discharge Cost-effectiveness Economic analysis Budget impact analysis

Leistungserbringer im deutschen Gesundheitswesen - Meier, Florian; Kast, Kristina; Schöffski, Oliver (Handbuch Gesundheitssoziologie, 2017)

Long-term care in Germany: State and visibility of current research activities on institutional long-term care for older adults Pflege in Deutschland: Stand und Sichtbarkeit der aktuellen Forschungsaktivitäten zur stationären Langzeitpflege von älteren Menschen - Kast, Kristina; Müller, Valesca; Drach, Cordula (2023)
Background A strong nursing research is essential for good care of people dependent on nursing care. However, nursing research in Germany is still at the beginning of its development compared to other countries. Objective In particular, the relevance of institutional long-term care for older adults will continue to grow. For this reason, we aimed to systematically assess the current state of research on this topic and to show its visibility. Methodology We conducted a systematic searched in various sources like homepages of research institutions, electronic databases, libraries, and scientific journals. We also included further sources like for example conferences or funding programs. We included research projects and publications about living in institutional long-term care facilities. We analyzed the data descriptively. Results We identified 94 research projects and 86 scientific publications. The average duration of a project was one year; most projects were led by universities and funded by government. A large number of projects did not involve collaborating partners. The states with the highest proportion of people dependent on care were more intensively involved in research. The projects had a wide range of topics. On average, less than one paper was published per project; over 70% had no publication. Conclusion To avoid losses in effectiveness and efficiency, more collaborative, focused research is needed. In addition, to achieve further development and keep pace with international research, the visibility of research must be improved. Zusammenfassung Hintergrund Für eine gute Versorgung von Pflegebedürftigen in der Praxis ist eine starke Pflegeforschung essentiell. Allerdings befindet sich Pflegeforschung in Deutschland im internationalen Vergleich noch am Anfang ihrer Entwicklung. Zielsetzung Da insbesondere die Relevanz der stationären Einrichtungen der Langzeitpflege von älteren Menschen weiterhin steigen wird, hat diese Arbeit zum Ziel, den Ist-Zustand der aktuellen Forschung zu diesem Thema systematisch zu erfassen und ihre Sichtbarkeit aufzuzeigen. Methodik Es fand eine systematische Recherche in verschiedenen Quellen statt. Durchsucht wurden Homepages von Forschungseinrichtungen, elektronische Datenbanken, Bibliotheken und Zeitschriften. Im Rahmen der Handsuche wurden weitere Quellen wie z.B. Konferenzen, Förderprogramme betrachtet. Gesucht wurde nach Projekten und Publikationen, die das Leben von älteren Menschen in stationären Einrichtungen der Langzeitpflege behandelten. Die Auswertungen erfolgten deskriptiv. Ergebnisse Es wurden 94 Projekte und 86 Publikationen identifiziert. Die durchschnittliche Projektlaufzeit lag bei einem Jahr, die Leitung lag überwiegend bei Universitäten, Finanzierung erfolgte meist aus öffentlichen Mitteln. Ein Großteil der Projekte hatte keinen Kooperationspartner. Bundesländer mit den meisten Pflegebedürftigen waren am stärksten in der Forschung involviert, thematisch ist eine breite Aufstellung ersichtlich. Im Schnitt wurde weniger als eine Publikation pro Projekt veröffentlicht. Über 70% hatten keine Veröffentlichung. Schlussfolgerung Um Effektivitäts- und Effizienzpotenzialverluste zu vermeiden, ist eine kooperationsintensivere, fokussierte Pflegeforschung wünschenswert. Um eine Weiterentwicklung zu erreichen und mit der internationalen Forschung mithalten zu können, muss außerdem die Sichtbarkeit der Forschung verbessert werden. <
Keywords: Institutional long-term care; nursing care research in Germany; stationäre Langzeitpflege; Pflegeforschung in Deutschland

Nutzung öffentlicher Qualitätsinformationen durch ältere Menschen: Können dadurch Qualitätsverbesserungen in Pflegeheimen erreicht werden? - Kast, Kristina; Pöthe, Soufian; Schöffski, Oliver (Gesundheitsökonomie und Qualitätsmanagement, 2025)
Zielsetzung Die Zielsetzung der Studie bestand darin, die Nutzung öffentlicher Qualitätsberichterstattung durch ältere Pflegeheimsuchende zu beurteilen und zu klären, ob diese mittels ihres Auswahlverhaltens zu Qualitätsverbesserungen in Pflegeheimen beitragen können. Methodik Es fand eine schriftliche Befragung von 57 älteren Menschen in 3 Pflegeheimen in Baden-Württemberg statt. Die Fragen bezogen sich auf Soziodemografie, die Kenntnis und Nutzung von Informationen von Internetvergleichsportalen sowie auf das Auswahlverhalten der Teilnehmenden. Ergebnisse Insgesamt wussten 66,7% der Teilnehmenden nicht, dass man sich online über Qualität informieren kann, 57,9% würden solchen Informationen nicht trauen und 21,1% würden ihre Entscheidung auf Basis von Internetinformationen überdenken. Schlussfolgerung Ältere Menschen alleine nutzen die Qualitätsinformationen nicht. Das Ziel einer Qualitätsverbesserung kann damit nicht erreicht werden. Sensibilisierung weiterer Zielgruppen für die Vorteile der Qualitätsberichterstattung und die Wichtigkeit einer gemeinsamen Pflegeheimsuche ist notwendi

Public Reporting über stationäre Pflegeeinrichtungen in Deutschland: Eine Bestandsaufnahme und Bewertung der Qualitätsinformationen Public Reporting on long-term Care Facilities in Germany: Current State and Evaluation of Quality Information - Kast, Kristina; Emmert, Martin; Maier, Claudia Bettina (Gesundheitswesen, 2020)

Smart Sensorik in der Schwangerschaft: Narratives Review über die Verlagerung der Schwangerschaftsvorsorge in den Smart Home Bereich Smart sensors in pregnancy: Narrative review on the use of smart home technology in routine prenatal care - Bossung, Verena; Kast, Kristina (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2021)
Introduction Today‘s routine prenatal care in Germany includes regular in-person appointments of pregnant women with doctors or midwives. Considering an increasing digitalization of the healthcare sector and in view of the global COVID-19 pandemic, the frequency of in-person visits could be reduced by remote monitoring using smart sensor technology. We aim to give an overview of the current international research on the use of smart sensors in prenatal care and its benefits, costs and resource consumption. Methods For this narrative review, PubMed and Science Direct were searched for clinical trials using smart sensors in prenatal care published in English or German language from 1/2016 to 12/2020. We included studies which addressed the benefits, costs and resource consumption of this innovative technology. Results We identified 13 projects using smart sensors in the fields of basic prenatal care, prenatal care for patients with hypertensive disease in pregnancy and prenatal care for women with gestational diabetes. The projects detected positive effects of smart sensors on health care costs and resource consumption and at least equal benefits for the pregnant women. Discussion and conclusions The current COVID-19 pandemic underlines the need for the introduction of smart sensor technology into German prenatal care routine. Remote monitoring could easily reduce the frequency of in-person visits by half. Smart sensor concepts could be approved as digital health applications in Germany. In order to increase user acceptance, there should not be any additional costs for pregnant women and health care professionals using modern healthcare apps. However, health insurance providers need to invest in smart sensor technology in order to eventually benefit from it.
Keywords: Pregnancy; Prenatal care; Smart sensor; Digitalization; Remote monitoring

Transitional Care Model in Germany: Findings from an economic analysis of a randomized controlled trial Das Transitional-Care-Modell in Deutschland: Erkenntnisse aus einer ökonomischen Analyse einer randomisierten, kontrollierten Studie - Kast, Kristina; Adelhardt, Thomas; Schöffski, Oliver (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2023)
Introduction: The statutory discharge management system in German hospitals does not provide adequate transitional care for geriatric patients. The American Transitional Care Model (TCM), where a qualified professional supports the patient for a period before, during, and after discharge, could help to address this problem. In this study, we compared both approaches from an economic perspective. Our research questions were: (1) How do treatment costs per person differ when geriatric patients are supported according to the TCM compared with routine discharge management? (2) What are the intervention costs? Methods: The present economic analysis was part of a randomized controlled trial conducted at a hospital in Germany. In this study, geriatric patients in the intervention group received care according to TCM and those in the control group received routine care. We obtained data from the hospital and a health insurance company. In a cost-cost analysis, we compared the treatment costs per patient incurred in both study groups. In cases where higher costs occurred in the intervention group, we also conducted a cost-utility analysis, using the 12-Item Short Form Survey questionnaire to collect quality-of-life data for the Quality Adjusted Life Years calculation. Intervention costs were calculated on the basis of staff salaries, working hours, and the cost of acquiring the necessary equipment. Results: The intervention group consisted of 109 geriatric patients, the control group of 119. The average quality-of-life score was slightly higher in the intervention group, but the difference was not significant. On average, the intervention group was less expensive. However, for individual cost types (e.g., rehabilitation), the intervention group incurred higher costs than the control group. The differences between the study groups were not significant for all cost types (p > 0.05). Intervention costs were estimated to be approximately 800 euros per patient. Discussion: The TCM approach leads to savings. However, the quantum of savings will depend on intervention costs, which vary in practice. After outlier exclusion, an unfavorable incremental cost-effectiveness ratio is observed for the TCM approach. Conclusion: From an economic perspective, TCM in its present form provides no additional value to patient care compared with routine discharge management. However, we see an urgent need to optimize the existing discharge management system to ensure better transitional care for those affected. Therefore, we recommend that different TCM components should be tested in further studies to address the questions that could not be clarified in the present study.
Created from Fastlane, Scopus look-up
Keywords: Cost analysis; Discharge management; Economic analysis; Geriatric; Transitional Care Model

Transition from hospital to nursing home: Discharge planners as a potential lever for quality improvements? Übergang vom Krankenhaus ins Pflegeheim: Entlassmanagementpersonal als Hebel für Qualitätsverbesserungen? - Kast, Kristina; Carl, Lukas (Zeitschrift für Gerontologie und Geriatrie, 2024)
Background Public reporting is supposed to be helpful in differentiating between well and poorly performing nursing homes; however, hospital patients often have difficulties to deal with quality information. Discharge planners (DP) can support them in comparing quality and, by influencing patients’ decision, lead to better provision of care in nursing homes. Objective This study investigated the choice behavior of DP, their use of quality information and the potential to impact the decision-making of patients. Material and methods A total of 70 DP from German hospitals with a geriatric department participated in an online survey. They were asked about information preferences and tools used for nursing home searches. In addition, they assessed quality information items from the new German quality reporting on a Likert scale. To test their comprehension participants were given a case scenario of a typical patient, were shown nursing homes displayed based on a medical comparison portal navigator (AOK-Pflegenavigator) and were asked to select nursing homes in a 3-round experiment. Results When looking for a nursing home, DP primarily rely on internal nursing home directories (n = 62; 92.5%). The 3 preferred criteria for decision are: distance to the family (n = 55; 28.80%), bed availability (n = 51; 26.7%) and wishes of patients/relatives (n = 41; 21.47%). The consent score for public reporting was 46.28% and the comprehension ratio was 82.24%. Discussion The DP do not advise hospital patients on the performance of nursing homes and rely on the decision-making of patients. This results in a lack of impact on patients’ decisions and consequently in a loss of potential for public reporting to lead to better care in nursing homes.
Keywords: Public reporting; Discharge management; Quality of care; Online survey; Quality representation agreement

Web-Based Public Reporting as a Decision-Making Tool for Consumers of Long-Term Care in the United States and the United Kingdom: Systematic Analysis of Report Cards - Kast, Kristina; Otten, Sara-Marie; Konopik, Jens; Maier, Claudia Bettina (JMIR Formative Research, 2023)
Background: Report cards can help consumers make an informed decision when searching for a long-term care facility. Objective: This study aims to examine the current state of web-based public reporting on long-term care facilities in the United States and the United Kingdom. Methods: We conducted an internet search for report cards, which allowed for a nationwide search for long-term care facilities and provided freely accessible quality information. On the included report cards, we drew a sample of 1320 facility profiles by searching for long-term care facilities in 4 US and 2 UK cities. Based on those profiles, we analyzed the information provided by the included report cards descriptively. Results: We found 40 report cards (26 in the United States and 14 in the United Kingdom). In total, 11 of them did not state the source of information. Additionally, 7 report cards had an advanced search field, 24 provided simplification tools, and only 3 had a comparison function. Structural quality information was always provided, followed by consumer feedback on 27 websites, process quality on 15 websites, prices on 12 websites, and outcome quality on 8 websites. Inspection results were always displayed as composite measures. Conclusions: Apparently, the identified report cards have deficits. To make them more helpful for users and to bring public reporting a bit closer to its goal of improving the quality of health care services, both countries are advised to concentrate on optimizing the existing report cards. Those should become more transparent and improve the reporting of prices and consumer feedback. Advanced search, simplification tools, and comparison functions should be integrated more widely.<br
Keywords: long-term care; medical decision-making; nursing homes; public reporting; quality improvement; report cards

What do people really want to know when searching for a long-term care facility? A systematic-narrative hybrid literature review of stated consumer information preferences for public reporting - Kast, Kristina (2025)
Background and objective Providing relevant quality information on public report cards can inform the consumer choice of healthcare providers. However, it is unclear what information people without expert knowledge need when searching for a long-term care facility. The present review aimed to summarize existing findings on people’s information preferences and provide a basis for the design of public report cards. Methodology This study is a systematic-narrative hybrid literature review. A literature search of PubMed and ScienceDirect was conducted for articles published between 2001 and 2022. Studies that referred to long-term care and included participants who were uninstitutionalized people over 65 years or their representatives were eligible; participants expressed their preferences in own words and had no professional experience in searching for a facility. Studies concerning acute care or end-of-life care facilities and studies where participants had to assess predefined preferences were excluded. The preferences stated in interviews were extracted in the exact format they occurred in the results tables in the studies and analyzed using a hybrid data synthesis strategy. First, doing a thematic analysis, preferences were grouped inductively into categories across the studies to show what information people desire. Second, in the deductive approach, preferences were assigned to Donabedian’s structure-process-outcome domains to show what information should be included on public report cards. Results Out of 27,197 articles identified in the period of the past 20 years, only a Belgian study and a US study were eligible. Three essential preferences dimensions with nine information types were identified. People want to be able to get own impression about a facility (e.g., information types like living, place, support), to learn about external evaluations (e.g., experiences, inspections) and to assess the realizability of their potential choice (e.g., affordability). The deductive approach showed how the nine information types are spread across the structure-process-outcome domains. Conclusion This review provided important insights into consumers’ perspective. The tree dimensions with nine information types show that people want to be able to assess the whole situation that awaits them, when they search for a “new home”. To be helpful for consumers, current public report cards should be substantially supplemented by the information identified in this revie
Keywords: Quality reportiing; information release; decision-making; provider choice; nursing homes

Wie können Potenziale von internet- und mobilbasierten Interventionen in der Versorgung von Depressionen genutzt werden? Erkenntnisse aus einer qualitativen Befragung deutscher Psychotherapeut*innen How can the potential of internet- and mobile-based interventions be used in the treatment of depression? Findings from a qualitative survey among German psychotherapists - Karch, Julia; Kast, Kristina (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2024)
Zusammenfassung Hintergrund und Zielsetzung Internet- und mobilbasierte Interventionen (IMIs) können das Versorgungsdefizit bei der Behandlung von Menschen mit Depressionen reduzieren. Für die Implementierung spielen die Leistungserbringenden als zentrale Figuren auf dem Gesundheitsmarkt eine wesentliche Rolle. Ziel dieses Beitrags ist es daher, die Barrieren, Treiber und Erwartungen aus Sicht von Psychotherapeut*innen zu untersuchen. Methode Es wurden im Raum Nürnberg n = 15 Psychotherapeut*innen anhand eines nicht-standardisierten Leitfadens interviewt. Die Daten wurden anschließend nach den Prinzipien der Grounded Theory qualitativ ausgewertet. Ergebnisse Vorteile wurden vor allem im Bereich der Optimierung des Patient*innennutzens und in der Überbrückung von Wartezeiten sowie der Nachsorge gesehen. Herausforderungen bestehen in Bezug auf unzureichende Informations- und Kommunikationswege zwischen den Beteiligten auf dem Gesundheitsmarkt und den daraus resultierenden fehlenden Erfahrungen mit IMIs auf Seiten der Behandelnden. Diskussion Für eine verstärkte Implementierung von IMIs in die Versorgung von Menschen mit Depressionen müssen neben den Treibern und Barrieren unterschiedliche Handlungsfelder berücksichtigt werden: die Art und Weise der Integration in den Behandlungsprozess, die Konzeption von IMIs und die Beziehungen auf dem Gesundheitsmarkt. Ausschlaggebend ist dabei eine verstärkte Zusammenarbeit aller Beteiligten auf dem Gesundheitsmarkt. Schlussfolgerung Die identifizierten Barrieren bestehen vor allem aufgrund unzureichender Informations- und Kommunikationswege innerhalb des Gesundheitsmarktes. Sie sind wichtige Anhaltspunkte, wie eine verstärkte Implementierung von IMIs in den Behandlungsprozess bei der Versorgung von Depressionen gelingen kann. Abstract Introduction and Objectives Internet and mobile-based interventions (IMIs) can reduce the unmet need for treatment of people with depression. The service providers as key actors in the healthcare market play an essential role in implementation. Therefore, the barriers, drivers and expectations from the perspective of psychotherapists were examined. Methods In the Nuremberg area, n = 15 psychotherapists were interviewed using a semi-structured guideline. The data were then evaluated according to the principles of Grounded Theory. Results Primarily, optimizing patient benefits and bridging waiting times and aftercare were seen as advantages. Challenges exist in relation to insufficient information and communication channels between those involved in the healthcare market and the resulting lack of therapists' experiences with IMIs. Discussion In addition to the drivers and barriers, different fields of action must be taken into account in order to increase the implementation of IMIs in the care of people with depression; these include the way that IMIs are integrated into the treatment process, the conception of IMIs and the relationships on the healthcare market. The decisive factor here is to increase cooperation between all those involved in the healthcare market. Conclusion The barriers identified are mainly due to insufficient information and communication channels within the healthcare market. They provide helpful guidance for understanding how the increased implementation of IMIs into the care process in the treatment of depression can succeed. <p
Keywords: E-Mental Health; Depression; Internet- und mobilbasierte Interventionen; Digitalisierung; Psychotherapie; Internet- and mobile-based interventions; Digital health; Psychotherapy